Isolated nocturnal hypertension and target organ damage in a population of African descent - Phukubje, Edgar Matome (University of the Witwatersrand, Johannesburg, 2024)
The use of ambulatory blood pressure monitoring (ABPM) has revolutionised the approach to hypertension diagnosis and management. The ability to monitor blood pressure over a 24-hour period has enabled researchers to monitor blood pressure profile away from the doctor’s clinic, which has led to the diagnosis of various hypertension phenotypes like masked hypertension, isolated nocturnal hypertension (INH) and isolated daytime hypertension (IDH), and others. Previous studies have shown that night-time blood pressure is more closely related to target organ damage compared to daytime blood pressure. Since more studies indicate that people of African ancestry have elevated night-time blood pressure compared to other population groups, nocturnal blood pressure monitoring in this population group is crucial. However, there are few studies that have investigated the prevalence of INH, and their results are inconclusive. Hence the impact of INH on cardiovascular target organ damage is not well understood in this population group. It has been reported that dietary salt intake (DSI) has more severe cardiovascular outcomes in African populations compared to non-African populations groups because they are said to be salt sensitive. However, there are no studies that have investigated the relationship between 24-hour urinary salt excretion and 24-hour dipping patterns in populations of African ancestry. In addition, the impact of INH on target organ damage has never been compared to that of IDH. Hence, current intervention strategies primarily rely on daytime blood pressure to diagnose and treat hypertension. The relationship between age and blood pressure is well understood, but current studies have mainly focused on daytime blood pressure. The impact of age on nocturnal blood pressure is not well understood in this population group, and it is also unclear whether the age-related changes in nocturnal blood pressure translate to any cardiovascular target organ changes. Therefore, the aim of this study was to determine the relationship between INH and cardiovascular target organ damage in a South African population of African ancestry. A total 1600 participants above 18 years were recruited. These form part of the ongoing South African Hypertension and Diet Study in the Human Nutrition Research Laboratory. Office blood pressure was measured conventionally and through SpaceLabs ambulatory oscillometric monitors for 24-hours. Target organ function was determined through echocardiographic measurements and applanation tonometry using the sphygmocor device. 24-hour urine samples were collected to determine electrolyte excretion rates. Blood was collected when the participants visited the clinic. Only data with complete 24-hour ABPM matched with complete urinary collections were included for data analysis and the final sample was 796 participants. v Findings from the current study showed that 11% of the participants had INH, 13% had 24- hour sustained hypertension and 4% had IDH. The three groups had different dipping patterns. The sustained hypertensive group were non-dippers, IDH group were dippers, and the INH group had two dipping patterns: non-dipping (IND) and reverse dipping (IRD). Urinary electrolyte concentrations were significantly higher in IDH, and lower in INH. The INH group and 24-hour sustained hypertensives were the oldest cohort, while the NT and IDH were youngest. Pulse wave velocity (PWV) was significantly higher in the IND and IRD. The NT and IDH group had the lowest PWV. PWV in the INH was similar but not significantly different to the 24-hour sustained HT group. These findings indicate that the two INH subtypes (IND and IRD) damage large arteries to a similar effect as 24-hour sustained hypertension, while IDH does not cause any damage. The ABPM results were used to show changes in blood pressure with age. Different age group ranges were used, in increments of 10 years. Increased nocturnal blood pressure was associated with being older. Additionally, age-related changes in nocturnal blood pressure were associated with pre-clinical diastolic dysfunction. The current findings further show that blood pressure related cardiovascular target organ damage occurs during night-time in this population group. Urine analysis showed increased excretion in IDH and sodium retention in INH. Aldosterone levels were significantly higher in the INH, compared to 24-hour sustained HT group. Low aldosterone and salt retention increased nocturnal BP in the INH group. This means the current rise in the prevalence of cardiovascular disease in people of African descent despite increased efforts to diagnose and treat hypertension, is driven by INH, which remains undiagnosed because of the over reliance on conventional blood pressure measurement
A research report submitted in fulfillment of the requirements for the Doctor of Philosophy, in the Faculty of Health Sciences, School of Physiology, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Isolated nocturnal hypertension; Reverse dipping; Vascular damage; Arterial stiffness; Isolated daytime hypertension; Non-dipping; SDG-3: Good health and well-being